A hybrid MARWIP-CODAS techniques for optimizing sourcing decisions in complex Fermatean fuzzy N soft sets - Anukokila Paraman; Nishanthini Rajendran; Radhakrishnan Bheeman (Journal of Fuzzy Extension and Applications)
This study aims to model a hybrid multi-criteria group decision-making process that combines the fundamental characteristics, operational laws and aggregation operators of interval valued complex Fermatean fuzzy $N$ soft sets with their empirical core concepts. To begin, we propose an integrated rank sum and a method based on the removal effects of criterion approaches to establish the weighting procedure, which is subsequently applied to the combinative distance-based assessment technique to rank the alternatives. Furthermore, we employ the hybrid decision-making approach to an IVCFFNs environment to deal with complex uncertainty information in real-world decision-making problems. In addition, to illustrate the utility and uniqueness of this approach, the proposed model is adapted to supplier selection problem and the obtained results are compared with other standard group decision-making methods.